2016
DOI: 10.1016/j.dmpk.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the plasma fentanyl and serum 4β-hydroxycholesterol based on CYP3A5 genotype and gender in patients with cancer pain

Abstract: This study aimed to evaluate the relationship between the concentrations of plasma fentanyl and serum 4β-hydroxycholesterol based on CYP3A5 genotype and gender in cancer patients. Thirty-three Japanese cancer patients treated with transdermal fentanyl were enrolled. The concentrations of plasma fentanyl and norfentanyl, and serum 4β-hydroxycholesterol and total cholesterol were determined at day 8 or later after starting the medication. The plasma fentanyl concentration was significantly higher in the CYP3A5*3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
1
17
3
Order By: Relevance
“…CYP3A5-deficient patients had close to double the plasma concentrations of some CYP3A5 substrates. 12,13 The CYP3A5 genotype had no relationship with the metabolic ratios of tolvaptan in the present study. These data indicate that CYP3A5 participates in both the production and elimination of the tolvaptan metabolites.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…CYP3A5-deficient patients had close to double the plasma concentrations of some CYP3A5 substrates. 12,13 The CYP3A5 genotype had no relationship with the metabolic ratios of tolvaptan in the present study. These data indicate that CYP3A5 participates in both the production and elimination of the tolvaptan metabolites.…”
Section: Discussioncontrasting
confidence: 66%
“…27 The CYP3A5*1 allele carriers had 1.5 times higher plasma 4β-OHC and 1.7 times higher plasma 4β-OHC/TC in cancer patients. 13 In the present study population, plasma 4β-OHC may not be useful for clear discrimination of the homozygous CYP3A5*3 allele. The plasma 25-OHD level was not different between the CYP3A5 genotypes.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…19,20) However, in a systematic review and meta-analysis, Gupta et al reported there was no significant association between postoperative opioid-induced respiratory depression and sex. 21) In the present study, the ROR trend for each opioid for sex varied. RORs of six opioids exceeded 1, suggesting respiratory depression related with these opioids may occur preferentially in males compared with females, while three opioids showed the opposite tendency.…”
Section: Discussionmentioning
confidence: 71%